Flow diversion to treat aneurysms: the free segment of stent. (10th July 2012) - Darsaut, Tim E; Bing, Fabrice; Makoyeva, Alina; Gevry, Guylaine; Salazkin, Igor; Raymond, Jean
Abstract : Purpose: Flow diverters (FDs) have led to spectacular results in otherwise untreatable aneurysm cases, but complications can occur. There is a pressing need to study factors that might predict their safety and efficacy. Methods: The anatomical constraints that may impact on the ability of FDs to redirect blood flow and provide a scaffold for neointima formation across the aneurysm or branch ostia are explored and classified. A nomenclature is needed to identify the key factors that should be taken into account before contemplating the use of FDs in clinical aneurysms, and that should be reproduced in experimental models, if they are to guide safe clinical use. Results: The free stent segment (FSS), the portion of the device that covers an aneurysm or branch origin, dictates whether aneurysms or branches will remain patent. Three levels of increasing complexity must be taken into account to anticipate what will occur at the FSS level. (1) Virtual models can provide basic principles; (2) in vitro studies allow testing FSS deformations that may occur in various anatomical circumstances and impact on efficacy and safety; (3) but only in vivo studies can provide key information on neointimal closure following implantation that will differentiate success from failure. Conclusions: A nomenclature is necessary to determine the optimal or suboptimal conditions for FDs and to design the virtual, in vitro and in vivo studies that will allow a better understanding of the factors involved in the success or failure of this novel treatment.